Analisis kemampuan pemecahan masalah matematis pada model problem based learning berbantuan scratch ditinjau dari motivasi belajar siswa - Lili Rahmawati; Mulyono Mulyono; Zaenuri Zaenuri; Walid Walid (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study was motivated by the low mathematical problem-solving ability of students. The aim of this research was to describe students’ mathematical problem-solving abilities in terms of learning motivation within PBL assisted by Scratch. This study employed a descriptive qualitative method with a case study design involving 26 eighth-grade students of SMP Negeri 7 Satu Atap Salem. Six students representing high, medium, and low learning motivation categories were selected through purposive sampling as interview participants. Data were collected using a learning motivation questionnaire, a mathematical problem-solving test consisting of five essay questions based on NCTM indicators, and interviews. The results showed differences in the characteristics of problem-solving abilities based on learning motivation levels. Students with high motivation were able to fulfill all indicators, while students with medium and low motivation still experienced difficulties, particularly in adjusting solution strategies and reflecting on their results. This study provides an overview of students’ mathematical problem-solving abilities based on learning motivation in PBL assisted by Scratch learning.